Long term dual antiretroviral therapy: A real life retrospective countrywide Israeli study. - Daniel David; Eynat Kedem; Dan Turner; Itzchak Levy; Daniel G Elbirt; Eduardo Shahar; Valery Istumin; Orna Mor; Michal Chowers; Hila Elinav (PLoS ONE, 2021)
Aim Combined antiretroviral treatment (cART) traditionally consists of three antiretroviral medications, while two-drug regimens (2DR), historically used infrequently, recently been suggested to be non-inferior to three-drug regimens, is emerging as a potential treatment option and is currently a recommended option for treatment initiation in many guidelines. Purpose Characterize the indications and clinical efficacy of 2DR use at a real-life setting in a nation-wide survey. Methods A cross-sectional survey of Israeli patients treated by 2DR until July 2019, included demographic, immunologic, virologic, genotypic and biochemical/metabolic parameters at diagnosis, ART initiation, 2DR initiation and following 24, 48, 96 and 144 weeks of 2DR treatment. Results 176 patients were included in the study. In contrast to historical data implicating ART resistance and adverse effects as the major reasons leading to 2DR switching, treatment simplification was the main reason leading to 2DR treatment in 2019. 2DR that included INSTI and PI were more commonly used in cases of drug resistance, while a combination of INSTI and NNRTI was used in all other 2DR indications. A switch to 2DR induced a mean CD4 T cell increase from 599 cells/μl at treatment initiation to 680 cells/μl at 96 weeks of treatment p<0.001 and viral suppression improvement from 73.9% at initiation to 87.0% at 48 weeks of treatment (p = 0.004). PI and INSTI 2DR was inferior in suppressing viral levels compared to other 2DRs but used for subset of more complex patients. Conclusions 2DR in a large-scale real-life nation-wide survey proved to be safe and effective. Most 2DRs, other than PI and INSTI, were similarly effective in suppressing HIV viremia and in elevating CD4 T cell counts.